Health problems in children and associated remedial measures in Punjab, India - Balpreet Singh1,; Abhik Ghosh2,; Amarjeet Singh3, (Universiti Kebangsaan Malaysia, 2015)
Background: Majority of child deaths that occur worldwide are due to preventable causes. Maternal practices regarding children’s health care have been recognized as an important factor behind mortality. Improving families’ care-seeking behavior can significantly reduce child morbidity and mortality in developing countries. Objective: To look into the prevalence of health problems in children and action taken by mothers for management of these problems. Materials and Methods: This cross-sectional study was conducted in three districts of Punjab, India. Mothers of children of age 12–23 months were selected. Sample size was calculated to be 1266 mothers. Multistage sampling was administered to identify study subjects. Semi-structured tool was used to get information regarding experiences of any health problems of children in the 15 days preceding the survey. Data were analyzed using Microsoft Office Excel 2007. Results: More than one third of children had health problems in the 15 days preceding the survey. The most common problems found were cold and cough, crying for unknown reasons, and fever. Majority (71.5%) of mothers took their children to health-care facilities to seek care. Private health-care facilities were used more than their public counterparts. Approximately 54% children were given home remedies. Majority of mothers used home remedies on the day problems appeared and visited health-care facilities on second or third day of the onset of problems. Conclusion: Home remedies were the first choice of many mothers for the illness of their children. Children with diarrhea and fever were more likely to be taken to health-care facilities